Pendidikan Karakter Pada Generasi Milenial di Lingkungan Kampus - Amir, Muhamad Abdul Azis Amir (Ma'soem University, 2021)
Advances in science and technology bring rapid changes both physically and psychologically. This results in positive and negative impacts on every aspect of life including the behavior or attitudes of society including the millennial generation as the main users of technological advances. Changes in people's attitudes, namely the millennial generation, need careful attention and handling, especially for changes that have a negative impact, one of which is leaving the values ??of the cultural character of the nation and the State. This phenomenon finally makes character education one of the main discourses in the national policy in the field of character education. The implementation of education by developing character values ??that are considered faded include integrity, religion, mutual cooperation, nationalism, and independence. The national character values ??that are starting to fade, especially in the millennial generation, must be addressed comprehensively so that they will have a more positive and dignified impact on the nation by educating, one of the educational methods, namely, community service with the Webinar method, which is held in collaboration between the Ma'soem University campuses. and STikom IM and Stie IM with the subject of the participants being millennial generation students and the general public. This webinar activity in community service uses the method of educating, familiarizing, and understanding the philosophical values ??of education, namely the character set forth in accordance with the philosophical values ??of the character of one of the founders of the Indonesian nation's education Ki Hajar Dewantara. The value of its educational character is exercise of the heart, thought, exercise, and initiative. This method will have an impact on the personality of the community, especially the millennial generation who will have character values ??such as integrity, religion, mutual cooperation, nationalism, and independence which are well crystallized and supported by the values ??of Pancasila. The results of the community service webinar with understanding approaches and methods, and education in the webinar, the millennial generation is felt to be able to understand character education that must be applied in their lives by starting from themselves, small things and starting from now on.